Genome-wide identification and oxacillinase OXA distribution characteristics of Acinetobacter spp. based on a global database - Li, Jia; Li, Yang; Cao, Xiaoli; Zheng, Jie; Zhang, Yan; Xie, Hui; Li, Chuchu; Liu, Chang; Shen, Han (Frontiers in Microbiology, 2023)
Objective: To use genomic analysis to identify Acinetobacter spp. and to explore the distribution characteristics of ß-lactamase oxallicinases (blaOXA) among Acinetobacter species globally. Methods: Genomes of global Acinetobacter spp. were downloaded from GenBank using Aspera batch. After quality check using CheckM and QUAST software, the genomes were annotated using Prokka software to investigate the distribution of blaOXAs across Acinetobacter spp.; a phylogenetic tree was constructed to explore the evolutionary relationship among the blaOXA genes in Acinetobacter spp. Average-nucleotide identification (ANI) was performed to re-type the Acinetobacter spp. BLASTN comparison analysis was implemented to determine the sequence type (ST) of Acinetobacter baumannii strain. Results A total of 7853 genomes were downloaded, of which only 6639 were left for further analysis after quality check. Among them, 282 blaOXA variants were identified from the genomes of 5893 Acinetobacter spp.; blaOXA-23 (n = 3168, 53.8%) and blaOXA-66 (2630, 44.6%) were the most frequent blaOXAs, accounting for 52.6% (3489/6639), and the co-carriage of blaOXA-23 and blaOXA-66 was seen in 2223 (37.7%) strains. The 282 blaOXA variants were divided into 27 clusters according to the phylogenetic tree. The biggest clade was blaOXA-51-family carbapenem-hydrolyzing enzymes composed of 108 blaOXA variants. Overall, 4923 A. baumannii were identified out of the 6639 Acinetobacter spp. strains and 291 distinct STs were identified among the 4904 blaOXA-carrying A. baumannii. The most prevalent ST was ST2 (n = 3023, 61.6%) followed by ST1 (n = 228, 4.6%). Conclusion OXA-like carbapenemases were the main blaOXA-type β-lactamase spread widely across Acinetobacter spp. Both blaOXA-23 and blaOXA-66 were the predominant blaOXAs, among all A. baumannii strains, with ST2 (belonging to CC2) being the main clone disseminated globally.